DESKRIPSI KEMAMPUAN MATEMATIKA DAN KORELASINYA DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS X MIPA SMA NEGERI 4 PONTIANAK - Eka Kurniawati; Tuti Kurniati; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACT Learning chemistry is a combination of theories with calculation that require good mathematical abillity in solving problems. This research was investigate and examined the student’s mathematic skill and correlation of the results class X MIPA SMA Negeri 4 Pontianak. This research was a correlation study. The selected samples consisted of 69 students in the class X MIPA 3 and MIPA 4 used Random Sampling technique. The data ware obtained using mathematical skill tests, documentation of the value of the results of class X student second semester of 2015/2016 and interview. This research was indicates that students with high math skills, students achievment chemical is no longer influenced by mathematical abilities. Data were analyzed with a nonparametric test (Spearman Rank test) showed there is no significant correlation between the skill of mathematics to chemistry student learning achievment at 0.236 and correlation coefficient of 0.145 including very low category. The skill of Mathematics class X SMAN 4 Pontianak totaling 69 students were good to excellent category the percentage of students 53.6%, 40.5% good category, the category was sufficient 4.5%, 1.4% less category.Keywords: Corellation, Mathmatics skill, Student’s learning achievement chemistry